Impact of Cooling Strategies on Transfusion Requirements in Aortic Hemiarch Surgery - Norman, Anthony V.; Challa, Sanjana; Lyons, Genevieve; Wisniewski, Alexander M.; Strobel, Raymond J.; Mazzeffi, Michael; Joseph, Mark; Tang, Daniel; Singh, Ramesh; Kontos, Michael C.; Quader, Mohammed; Yount, Kenan; Teman, Nicholas R.; Preventza, Ourania; Beller, Jared P. (AORTA, 2025)
Deep hypothermic circulatory arrest (DHCA) is associated with coagulopathy but facilitates aortic arch surgery. Conflicting data suggest moderate hypothermic circulatory arrest (MHCA) may reduce transfusion requirements. We hypothesized MHCA would reduce transfusion requirements.We studied patients undergoing aortic hemiarch surgery for nondissected, aneurysmal disease from July 2014 to May 2023 utilizing a multicenter collaborative. Patients were stratified by DHCA (14.1–20°C) and MHCA (20.1–28°C). Packed red blood cells (pRBC), fresh frozen plasma (FFP), cryoprecipitate, and platelet transfusion requirements were assessed. A negative binomial model accounting for hospital random effect was fitted to identify risk factors for increased transfusion requirements.Of the 451 patients undergoing hemiarch surgery, 373 (83%) had MHCA and 78 (17%) had DHCA. MHCA patients had shorter cardiopulmonary bypass (135 minutes [105, 182] vs. 216 minutes [183, 263], p < 0.001) and circulatory arrest times (12 minutes [8, 17] vs. 21 minutes [16, 34], p < 0.001). MHCA patients received fewer pRBC (0 [0, 1] vs. 1 [0, 3], p < 0.001), FFP (0 [0, 3] vs. 2 [0, 4], p = 0.003), cryoprecipitate (1 [0, 1] vs. 1 [0, 2], p = 0.045), and platelet transfusions (0 [0, 1] vs. 2 [0, 2], p < 0.001). Unadjusted operative mortality was lower in the MHCA group (1.9 vs. 7.7%, p < 0.01). After risk adjustment, MHCA was associated with reduced FFP transfusion requirements (β = −0.48, SE = 0.2, p = 0.017). Increasing bypass time per minute was associated with increased pRBC (β = +0.01, 95% CI = 0.006–0.013, p < 0.001), FFP (β = +0.006, 95% CI = 0.004–0.009, p < 0.001), cryoprecipitate (β = +0.008, 95% CI = 0.005–0.01, p < 0.001), and platelet transfusions (β = +0.009, 95% CI = 0.006–0.011, p < 0.001).MHCA was associated with decreased mortality and FFP transfusions in aortic hemiarch repair. MHCA may mitigate transfusion needs via shorter cardiopulmonary bypass time compared with DHCA.
Keywords: hypothermia; circulatory; blood; transfusion; aorta